2013
DOI: 10.1021/bm4015232
|View full text |Cite
|
Sign up to set email alerts
|

Gelation Chemistries for the Encapsulation of Nanoparticles in Composite Gel Microparticles for Lung Imaging and Drug Delivery

Abstract: The formation of 10 to 40 μm Composite Gel MicroParticles (CGMPs) comprising ~100 nm drug containing nanoparticles (NPs) in a poly(ethylene glycol)(PEG) gel matrix is described. The CGMP particles enable targeting to the lung by filtration from the venous circulation. UV radical polymerization and Michael addition polymerization reactions are compared as approaches to form the PEG matrix. A fluorescent dye in the solid core of the NP was used to investigate the effect of reaction chemistry on the integrity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
(156 reference statements)
0
16
0
Order By: Relevance
“…With the universal curve presented here for particle compression, it is now possible to quantify the poroelastic properties of biological entities such as cells, which have been shown to behave poroelastically 45 , and hydrogel particles for drug delivery in vivo 9,12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the universal curve presented here for particle compression, it is now possible to quantify the poroelastic properties of biological entities such as cells, which have been shown to behave poroelastically 45 , and hydrogel particles for drug delivery in vivo 9,12 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, hydrogel particles hold great promise for use as controlled drug delivery systems due to their biocompatibility, ease of manufacture, and precise control of strength and size [8][9][10] . Control of size and strength is critically important for successful delivery of active ingredients in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note is the dye photostabilization afforded by trapping the dye in a solid state within the CNC core, which minimizes photoinduced degradation . Previous work has demonstrated that fluorophores in CNC cores undergo only minor photobleaching when exposed to intense UV or blue–green light . This robustness ensures minimal degradation of the CNC fluorescence signal during extended imaging experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Recent examples of NCI-supported progress for clinical applications span the development of novel diagnostic assays, 50,51 in vivo imaging tools, 52-57 novel drug delivery tools, [58][59][60][61][62][63] new cytotoxic agents 64,65 and so-called theranostic platforms (bearing combined therapeutic and diagnostic capabilities). [66][67][68][69] Furthermore, NCI manages a 36 Cooperative nanoparticles for amplified tumor targeting…”
Section: Other Nanotechnology Efforts Within Ncimentioning
confidence: 99%